Fundamentals and recent advances in X-ray micro computed tomography (microCT) applied on thermal-fluid dynamics and multiphase flows. (October 2015) - Santini, Maurizio
Abstract: X-ray computed tomography (CT) is a well-known technique nowadays, since its first practical application by Sir. G. Hounsfield (Nobel price for medicine 1979) has continually benefited from optimising improvements, especially in medical applications. Indeed, also application of CT in various engineering research fields provides fundamental informations on a wide range of applications, considering that the technique is not destructive, allowing 3D visualization without perturbation of the analysed material. Nowadays, it is technologically possible to design and realize an equipment that achieve a micrometric resolution and even improve the sensibility in revealing differences in materials having very radiotransparency, allowing i.e. to distinguish between different fluids (with different density) or states of matter (like with two-phase flows). At the University of Bergamo, a prototype of an X-ray microCT system was developed since 2008, so being fully operative from 2012, with specific customizations for investigations in thermal-fluid dynamics and multiphase flow researches. A technical session held at the UIT International Conference in L'Aquila (Italy), at which this paper is referring, has presented some microCT fundamentals, to allow the audience to gain basics to follow the "fil-rouge" that links all the instrumentation developments, till the recent applications. Hereinafter are reported some applications currently developed at Bergamo University at the X-ray computed micro-tomography laboratory.